Development of a Test-Rig for a Modern Motorcycle Engine - Hamada, K. I.; Mohammed, M. K.; M. M., Rahman (Universiti Malaysia Pahang, 2014)
This paper presents experimental activities that have been performed in the Automotive Engineering Centre laboratories in Universiti Malaysia Pahang for developing a test-rig based on a modern motorcycle engine. The experimental engine test-rig was developed based on an eddy current dynamometer which was coupled to a four-stroke single-cylinder SI motorcycle engine. Moreover, the test-rig consists of all the measurement equipment, sensors and auxiliaries kits for carrying out engine testing in a sufficient way. The results of these activities have been used for validation of a one-dimensional model developed based on that single cylinder engine. Both the in-cylinder pressure trace and brake torque were used to validate the engine model. There was good agreement between the simulation and experimental results. The constructed test-rig can be utilized for further research and development programs.